2014
DOI: 10.1590/s0100-736x2014000200008
|View full text |Cite
|
Sign up to set email alerts
|

Resistência contra ectoparasitas em bovinos da raça Crioula Lageana e meio-sangue Angus avaliada em condições naturais

Abstract: Pesq. Vet. Bras. 34(2):141-146, fevereiro 2014 141 RESUMO.-Este trabalho foi desenvolvido com o objetivo de avaliar a resistência aos ectoparasitas em bovinos jovens da raça Crioula Lageana e meio-sangue Angus em condições naturais. Foram utilizados 10 machos castrados em cada grupo, recém desmamados (6-8 meses) e mantidos sob as mesmas condições de manejo, em pastagens cultivadas de inverno e verão, no município de Monte Castelo -SC, sofrendo infestação natural por ectoparasitas. A cada 28 dias, fêmeas de car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Breeds of Bos indicus are genetically more resistant to ticks than Bos taurus due the presence of naturally selected genes throughout their evolutionary process (Ibelli et al, 2012;Ayres et al, 2015). Genetic variability for bovine tick resistance has been reported (Cardoso et al, 2014), showing potential for the improvement of this trait. According to Walker (2011), individual ability of cattle to acquire tick immunity is hereditary.…”
Section: Introductionmentioning
confidence: 99%
“…Breeds of Bos indicus are genetically more resistant to ticks than Bos taurus due the presence of naturally selected genes throughout their evolutionary process (Ibelli et al, 2012;Ayres et al, 2015). Genetic variability for bovine tick resistance has been reported (Cardoso et al, 2014), showing potential for the improvement of this trait. According to Walker (2011), individual ability of cattle to acquire tick immunity is hereditary.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that Crioulo Lageano cattle are more resistant to botflies and ticks than Aberdeen Angus cattle ( 43 ). These findings suggest that factors beyond genetics play a role in determining susceptibility to diseases like anaplasmosis and babesiosis.…”
Section: Discussionmentioning
confidence: 99%
“…After the desensitization, bleeding and skinning procedures, pieces of approximately 3.0 cm of the extensor carpi radialis muscle were collected and frozen in liquid nitrogen for the subsequent quantification of reactive oxygen species. Next, the number and location of hematomas in the carcasses were evaluated, dividing them into regions proposed by the methodology by Cardoso et al, [19].…”
Section: Methodsmentioning
confidence: 99%